Potential for cadaveric organ retrieval in New South Wales. Issue 6838 (23rd May 1992) - Hibberd, A. D.; Pearson, I. Y.; McCosker, C. J.; Chapman, J. R.; Macdonald, G. J.; Thompson, J. F.; O'Connell, D. L.; Mohacsi, P. J.; McLoughlin, M. P.; Spratt, P. M.
Abstract : OBJECTIVES--To measure the potential for cadaver organ retrieval in New South Wales and to determine the reasons for potential donors failing to become actual donors. DESIGN--Prospective audit of all patients dying in five hospitals in New South Wales between 1 December 1989 and 30 November 1990; quality assurance of the data by independent medical specialist and if disagreement by study committee. PATIENTS--2879 patients (100% of all deaths) yielding 364 patients with coma and 181 potential donors. OUTCOME MEASURES--Realistic medically suitable potential donor rate, missed potential donor rate, rate of potential donors with permission refused, donor rate, reasons for realistic medically suitable potential donors failing to become actual donors. RESULTS--2879 deaths yielded 73 medically suitable potential donors, resulting in 19 actual donors, 30 missed potential donors, 19 potential donors with permission refused, and five in whom adequate resuscitation failed. The most common reason for a potential donor failing to become an actual donor was a decision by the senior medical practitioner to withdraw or not to institute ventilatory or haemodynamic support (26/73). The second major obstacle was refusal of permission by the next of kin (17/73). Assuming that the potential donor rate was that implied by the observed donor rate (13/million population/year) the projected missed potential donor rate was 9/million population/year (95% confidence interval 4 to 15) and the projected rate of potential donors with permission refused was 13/million population/year (95% confidence interval 5 to 22). Assuming that the rate of potential donors in the study hospitals was the same as in the other New South Wales hospitals, the projected donor rate for New South Wales was 18/million population/year (10 to 26); the projected missed potential donor rate was 15/million population/year (7 to 23); and the projected rate of potential donors with permission refused was 18/million population/year (10 to 27). CONCLUSIONS--The donor rate could be increased 70%-80% by overcoming the reluctance of medical practitioners to resuscitate missed potential donors and increased further by gaining permission for organ retrieval from the next of kin.